ANALISIS INOVASI DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA WAKEUP COFFEE KEDIRI - Sidiq, Ahmad (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
The development of the business world is currently increasing very rapidly. One of them is in the culinary business sector. Competition is one thing that cannot be separated from business life. Currently, business competition is getting tougher and tougher, as is happening in Indonesia. Business competition in Indonesia has created many changes for business people. Many things influence the occurrence of competition, some of which are achievement targets, innovations in human life, the level of human creativity that continues to develop, the demands of life that continue to increase, and human lifestyles that continue to change in every era. The purpose of this study is to analyze (1) Innovation has a significant effect on WakeUp Coffee Kediri Consumer Satisfaction. (2) Prices significantly affect WakeUp Coffee Kediri Consumer Satisfaction. (3) Innovation and Price simultaneously significantly affect WakeUp Coffee Kediri Consumer Satisfaction. The population in this study are consumers of wakeup coffee. Respondents in this study were 40 people using the total sampling method. And analyzed by Multiple linear regression with the help of the SPSS Version 29 application. The conclusion of this study Innovation has a significant effect on WakeUp Coffee Kediri Consumer Satisfaction. (2) Prices have a significant effect on WakeUp Coffee Kediri Consumer Satisfaction. (3) Innovation and Price simultaneously have a significant effect on WakeUp Coffee Kediri Consumer Satisfaction.